Pengaruh Keunggulan Bersaing dan Minat Konsumen terhadap Keputusan Pembelian pada Meubel Istiqomah Tasikmalaya - Ari Mardhiyan; Budhi Wahyu Fitriadi; Depy Muhamad Pauzy (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research was conducted to determine the influence of Competitive Advantage and Consumer Interest on Purchasing Decisions on Istiqomah Tasikmalaya Furniture. The research method used is a survey method with a quantitative approach, data was obtained directly through questionnaires distributed to 90 respondents who were Istiqomah Tasikmalaya Furniture Consumers. The research technique used is multiple liner regression analysis. Based on the research results, it can be seen that Competitive Advantage and Consumer Interest simultaneously have a significant influence on Purchasing Decisions on Istiqomah Tasikmalaya Furniture. Competitive Advantage partially has a significant influence on Purchasing Decisions on Istiqomah Tasikmalaya Furniture, and Consumer Interest partially has a significant influence on Purchasing Decisions on Istiqomah Tasikmalaya Furniture.